Clinical nutrition in surgical oncology: Young AIOM-AIRO-SICO multidisciplinary national survey on behalf of NutriOnc research group - Marano, Luigi; Marmorino, Federica; Desideri, Isacco; Carbone, Ludovico; Rizzo, Alessandro; Salvestrini, Viola; Roviello, Franco; Cinieri, Saverio; Donato, Vittorio; De Luca, Raffaele; , NutriOnc Research Group; Sofia, Silvia; et al. (Frontiers in Nutrition, 2023)
Malnutrition is a common condition in cancer patients which is usually associated with functional limitations, as well as increased morbidity and mortality. Based on the support of the young sections of Italian Association of Medical Oncology (AIOM), Italian Association of Radiotherapy and Clinical Oncology (AIRO) and Italian Society of Surgical Oncology (SICO) merged into the NutriOnc Research Group, we performed a multidisciplinary national survey with the aim to define the awareness of nutritional issues among healthcare professionals delivering anticancer care. The questionnaire was organized in four sections, as follows: Knowledge and practices regarding Nutritional Management of cancer patients; Timing of screening and assessment of Nutritional Status; Nutritional Treatment and prescription criteria; Immunonutrition and educational topics. The modules focused on esophagogastric, hepato-bilio-pancreatic and colorectal malignancies. Overall, 215 physicians completed the survey. As regards the management of Nutritional Status of cancer patients, many responders adopted the ERAS program (49.3%), while a consistent number of professionals did not follow a specific validated nutritional care protocol (41.8%), mainly due to lack of educational courses (14.5%) and financial support (15.3%). Nearly all the included institutions had a multidisciplinary team (92%) to finalize the treatment decision-making. Cancer patients routinely underwent nutritional screening according to 57.2% of interviewed physicians. The timing of nutritional assessment was at diagnosis (37.8%), before surgery (25.9%), after surgery (16.7%), before radiochemotherapy (13.5%) and after radiochemotherapy (7%). Most of the responders reported that nutritional status was assessed throughout the duration of cancer treatments (55.6%). An important gap between current delivery and need of nutritional assessment persists. The development of specific and defined care protocols and the adherence to these tools may be the key to improving nutritional support management in clinical practice.